Investigation of Acoustic Emission Signal Generated in the Friction Pair Lubricated with Oils Containing Various Lubricity Additives - Jan Guzik; Małgorzata Wojtyniak; Sławomir Olszowski; Miłosz Marczak; Zbigniew Ranachowski (Engineering Transactions)
The energy supplied to the friction pair is dissipated producing mainly heat. However, a small part of it radiates in the form of transient elastic waves or in other words, as the acoustic emission (AE) signal. This article presents measurement results of the AE signal generated in the four-ball friction pair lubricated with oil containing chosen lubricity additives. Measurements of the AE signal have been performed in conditions of continuous load increase. Values of friction torque in the pair were recorded simultaneously with AE measurements. It is expected that diagnostic measurements of AE signal generated in friction pairs of working machinery will be possible soon.